The role of atria in ventricular fibrillation after continuous-flow left ventricular assist device implantation in ovine model - Yu, Xin-Yi; Shi, Jian-Wei; Rong, Yan-Sheng; Chen, Yuan-Lu; Liu, Tian-Wen; Zang, Yi-Rui; Fu, Ze-An; Zhang, Jie-Min; Han, Zhi-Fu; Liu, Zhi-Gang (Frontiers in Cardiovascular Medicine, 2023)
Objectives: This study attempted to discuss potential mechanisms driving pulmonary circulation during ventricular fibrillation (VF) following continuous-flow left ventricular assist device (CF-LVAD) implantation. Methods: An acute animal experiment was conducted in small-tailed Han sheep via implanting a CF-LVAD, with the pump speed set as 2,400 rpm. VF was induced following ventricular tachycardia using a temporary pacemaker to stimulate the right and left ventricular free walls. The central venous pressure (CVP), artificial vascular flow (AVF), pulmonary artery flow (PAF) and other major indicators were observed and recorded after VF. Results: Low-flow systemic and pulmonary circulation could be sustained for 60 min under VF with sinus atrial rhythm after CF-LVAD implantation. The CVP gradually increased. The mean AVF declined from 1.80 L/min to 1.20 L/min, and the mean PAF decreased from 1.62 L/min to 0.87 L/min. Under VF with atrial fibrillation, the systemic and pulmonary circulation couldn't be sustained. The CVP jumped from the 5 mmHg baseline to 12 mmHg, the mean AVF rapidly decreased from 3.45 L/min to 0.79 L/min, and the PAF declined from 3.94 L/min to 0.77 L/min. Conclusions: The atrial rhythm and function might be necessary for the circulation maintenance in patients with VF after CF-LVAD implantation.